EVALUATION THE ACTIVITY OF ANTIOXIDANTS AND REPRODUCTIVE PERFORMANCE FOR ALLIUM CEPA AND ALLIUM SATIVUM EXTRACTS ON MALES RATS TREATED WITH MYCOTOXINS. - Al-Delemi, Dhia Hussain Jassim; Kadhim, Abeer Sami (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
The present study has been designed to evaluate the beneficial effects of Allium cepa andAllium sativum extract upon Ochratoxin-induced hepatic toxicity, The study has been conductedon adult male rats during the period extended from February, 2017 to, July 2017. Fifty maturemale Wister rats (aged 90 days and weighted 190±10 g),were divided in to Five randomly equalgroups , the first served as negative control received only normal saline , the second as positive control received with contaminated with Asp. niger in diet as a single dose(2.5 mg/kg b.w). thirdgroup received with contaminated with Asp. niger as a single dose then treated after 2 days withAllium cepa (250 mg /kg b.w.) respectively orally through stomach tube during 42 days. fourthgroup received contaminated with Asp. niger as a single dose then treated after 2 days withAllium sativum (250 mg /kg b.w.) respectively orally through stomach tube for 42 days. Fifth group received contaminated with Asp. niger as a single dose then treated after 2 days withAllium cepa and Allium sativum together (250,250 mg /kg b.w.) respectively orally throughstomach tube during 42 days. males were anaesthetized (by injection i/p of 0.3ml ketamine + 0.1ml of xylazine /kg b. w. ip), blood samples were obtained from heart in non-heparinized tubes,Blood serum samples were separated for assessment of GOT, GPT, concentration, andassessment testosterone, FSH in blood serum. Under our experimental conditions, contaminatedwith Asp. niger resulted evidenced by statistically significant ncrease(p>0.05) in the activitiesof GOT, GPT in group 2 of just Ochratoxin compared with the control group, while in the thirdand fourth groups showed statistically significant decrease (p<0.05) in GOT, GPT level inBlood serum of contaminated with Asp. niger treated group compared with the control group,while in assessment of hormone shown in contaminated group showed decrease of this hormonesas for as in Allium cepa and Allium sativum groups increase in hormones and in combinationgroups was very high significant in hormones levels. After histological analysis of the groupcontaminated with Asp. niger proved change in the, after the gavage of (Allium cepa and Alliumsativum), and in testicular section was shown the effect of plants extract to repair of tissue. Theresults showed that there was an improvement in liver tissues after treatment with Allium cepaand Allium sativum.In present study we concluded to Allium cepa and Allium sativum together dose 250+250 mg/kgb.w. is better than dose 250mg/kg b.w. alone depending on results in recently study. weconcluded that the administration of (Allium cepa and Allium sativum) together act as antifungaland antioxidant for contaminated with Asp. niger in males rats.